Observation of the fatigue crack propagation rate of an aluminum alloy specimen under fatigue spectrum loadings - Abdullah, Shahrum; Zakaria, Kamarul Ariffin; Ghazali, Mariyam Jameelah (2012)
This paper presents an assessment on fatigue crack propagation (FCG) behavior and fractography observation for an aluminum alloy that was exposed under spectrum loadings. The FCG test has three types of cyclic loadings, namely, constant-amplitude loading (CAL) as well as high-to-low and low-to-high sequence loadings. All three have been performed on the Al6061-T6 specimens. The tests were performed using a 100 kN servo-hydraulic fatigue testing machine following an ASTM E647 standard. The results show that fatigue crack propagation and its fractography were influenced by the load interaction and the sequence, which affect the fracture behavior of aluminum alloys. The fracture surface exhibited irregular local striation spacings under the spectrum loading. Moreover, the micrographs show increased plasticity throughout the crack propagation compared to CAL.